(untitled) (Annals of Medical Research, 2023)
Aim: This study aimed to compare the surgical stress and immunoinflammatory response caused by proximal femoral nail (PFN) and hemiarthroplasty (HA) in patients with unstable intertrochanteric fractures. Materials and Methods: We retrospectively evaluated 344 patients who had undergone surgery for intertrochanteric fractures. Inclusion criteria were defined as being between the ages of 65 and 80, having an ASA score of 3, and the time between fracture formation and surgery being less than 72 hours. PFN was performed in 42 of the patients whereas HA was performed in 40 patients. In the two groups, data such as age, gender, pre-operative waiting and operation times, length of hospital stay, change in hemoglobin levels, and erythrocyte suspension (ES) need were recorded. Venous blood samples were collected from all the patients at the first admission to the emergency department after fracture, 6 hours after the operation, and 3 days after the operation. neutrophil-lymphocyte ratio (NLR) and systemic immune-inflammation index (SII) were compared between the two procedures at three different time points. Results: The age, gender distribution, and preoperative wait duration did not differ significantly (p>0.05) between the two groups. The operation duration, hospitalization duration, and number of ES use were significantly higher (p<0.05) in the HA group than in the PFN group. In both groups, NLR and SII values increased significantly (p<0.05) between the day 0 and the 3rd postoperative day. The postoperative day 0 NLR and SII values in the HA group were significantly higher than those in the PFN group (p<0.05). Conclusions: We conclude that the PFN procedure causes less surgical stress than HA; therefore, it is a safer procedure.